2018
DOI: 10.1016/j.seizure.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes more than 5 years after temporal lobe epilepsy surgery: Remarkable functional recovery when seizures are controlled

Abstract: Epilepsy surgery can be a successful treatment option for temporal lobe epilepsy but there are concerns about accelerated memory decline in long-term follow-up. Method: 161 adult operated (77 right, 84 left temporal resections) versus a heterogeneous group of 208 nonoperated patients with focal epilepsies were consecutively recruited and re-evaluated focusing on memory, executive functions, and vocational outcome after follow-up intervals of > 5 years (5-22 years, mean 8 ± 3 years). Results: Major losses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 26 publications
4
56
1
Order By: Relevance
“…Besides these differences, comparable scores of the QOLIE were found for the remaining subscales across both patient groups ( Fig. 2A; Grewe, et al Inspecting our individual patient's data revealed that in general, higher QoL-scores for the RP as compared to the NRP were found for the subgroup of the seizure-free patients (ID 7,8,9). In contrast, non-seizure-free RP (ID 4,5,6) had comparable or even lower QoL-scores than the NRP.…”
Section: Quality Of Life Subjective Memory and Depressionsupporting
confidence: 54%
See 4 more Smart Citations
“…Besides these differences, comparable scores of the QOLIE were found for the remaining subscales across both patient groups ( Fig. 2A; Grewe, et al Inspecting our individual patient's data revealed that in general, higher QoL-scores for the RP as compared to the NRP were found for the subgroup of the seizure-free patients (ID 7,8,9). In contrast, non-seizure-free RP (ID 4,5,6) had comparable or even lower QoL-scores than the NRP.…”
Section: Quality Of Life Subjective Memory and Depressionsupporting
confidence: 54%
“…2C). Likewise, cognitive complaints in the FLei (and the QOLIE-32) were particularly low for the seizure-free RP (ID 7, 8,9) who also demonstrated the lowest scores in almost all remaining subscales of the QOLIE-32. Conflicting results between our and Edelvik et al's study may emerge from methodological differences.…”
Section: Quality Of Life Subjective Memory and Depressionmentioning
confidence: 96%
See 3 more Smart Citations